Analisis User Experience User Aplikasi Shopee di STMIK Kharisma Makassar Menggunakan Metode Heuristic Evaluation - COANDY, RONALDO YUSUF; Yunus, Arfan; Marlina (KHARISMA Tech, 2024)
This study aims to analyze the User Experience of Shopee Application Users at STMIK KHARISMA Makassar using the Heuristic Evaluation Method. This research uses the Heuristic Evaluation method which is a method used to find problems in the interface design of an application and look for the positive side of the application. The data source of this research uses primary data, namely a questionnaire where the data collected is 40 respondents at STMIK KHARISMA Makassar and secondary data, namely literature studies or references from other journals. The results showed that Shopee users at STMIK KHARISMA Makassar were predominantly male compared to female Shopee users. This is because at STMIK KHARISMA Makassar the male population is greater than women. Of the 10 aspects of the Heuristic Evaluation method, only 1 aspect has a Minor Usability Problem or there are problems that interfere with user comfort with a severity rating of 2, or improvements are needed with a low priority level. And 8 other aspects are worth 1 or Cosmetic Problem meaning only problems that do not affect users, and 1 aspect with a value of 0 or Don't Agree which means there is no problem at all.